Proteomics and phosphoproteomics reveal key regulators associated with cytostatic effect of amino acid transporter LAT1 inhibitor. Issue 2 (19th December 2020) - Okanishi, Hiroki; Ohgaki, Ryuichi; Okuda, Suguru; Endou, Hitoshi; Kanai, Yoshikatsu
Abstract: L‐type amino acid transporter 1 (LAT1) is highly expressed in various cancers and plays important roles not only in the amino acid uptake necessary for cancer growth but also in cellular signaling. Recent research studies have reported anticancer effects of LAT1 inhibitors and demonstrated their potential for cancer therapy. Here, we characterized the proteome and phosphoproteome in LAT1‐inhibited cancer cells. We used JPH203, a selective LAT1 inhibitor, and performed tandem mass tag–based quantitative proteomics and phosphoproteomics on four biliary tract cancer cell lines sensitive to JPH203. Our analysis identified hundreds to thousands of differentially expressed proteins and phosphorylated sites, demonstrating the broad influence of LAT1 inhibition. Our findings showed various functional pathways altered by LAT1 inhibition, and provided possible regulators and key kinases in LAT1‐inhibited cells. Comparison of these changes among cell lines provides insights into general pathways and regulators associated with LAT1 inhibition and particularly suggests the importance of cell cycle–related pathways and kinases. Moreover, we evaluated the anticancer effects of the combinations of JPH203 with cell cycle–related kinase inhibitors and demonstrated their potential for cancer therapy. This is the first study providing the proteome‐wide scope of both protein expression and phosphorylation signaling perturbed by LAT1 inhibition in cancer cells. Abstract : Our study investigated anticancer effects caused by inhibition of L‐type amino acid transporter 1 (LAT1), which is highly expressed in cancers and plays important roles in the amino acid uptake as well as cellular signaling. The integrated proteomics and phosphoproteomics on four biliary tract cancer cell lines revealed altered biological pathways, possible regulators, and key kinases in LAT1‐inhibited cells. We found the importance of cell cycle–related pathways in LAT1‐inhibited cells and demonstrated the therapeutic potential of LAT1 inhibitor in combination with cell cycle–related kinase inhibitor in cancer treatment.